2016
DOI: 10.1371/journal.pone.0152399
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Isaria fumosorosea CCM 8367 and Steinernema feltiae Ustinov against Immature Stages of the Colorado Potato Beetle

Abstract: The Colorado potato beetle, Leptinotarsa decemlineata, has developed resistance to most registered pesticides and has become one of the most difficult insect pests to control. Development of new biopesticides targeting this pest might solve the resistance problem and contribute to sustainable crop production. Laboratory experiments were conducted to assess the efficacy of Isaria fumosorosea (syn. Paecilomyces fumosoroseus) strain CCM 8367 against L. decemlineata when applied alone or combined with the entomopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 63 publications
1
30
1
Order By: Relevance
“…Choo et al [65] also reported that the combination of S. carpocap1ae (Weiser) with B. brongniartii (Saccardo) Petch resulted in a significant increase in the mortality of oriental beetle, Exomala orientalis (Waterhouse) grubs compared to the application of fungus alone. Most recently the combined application of the fungus Ifr CCM 8367 with entomopathogenic nematodes increased the mortality of the Colorado potato beetle larva up to 98.0% compared to either entomopathogen applied alone [66]. Jabbour et al [67] concluded after investigating entomopathogen biodiversity and its effect on host mortality, that the combined pairings of fungal entomopathogens and entomopathogenic nematodes always produced host mortality that exceeded predictions based on the impact of either entomopathogen alone.…”
Section: Discussionmentioning
confidence: 99%
“…Choo et al [65] also reported that the combination of S. carpocap1ae (Weiser) with B. brongniartii (Saccardo) Petch resulted in a significant increase in the mortality of oriental beetle, Exomala orientalis (Waterhouse) grubs compared to the application of fungus alone. Most recently the combined application of the fungus Ifr CCM 8367 with entomopathogenic nematodes increased the mortality of the Colorado potato beetle larva up to 98.0% compared to either entomopathogen applied alone [66]. Jabbour et al [67] concluded after investigating entomopathogen biodiversity and its effect on host mortality, that the combined pairings of fungal entomopathogens and entomopathogenic nematodes always produced host mortality that exceeded predictions based on the impact of either entomopathogen alone.…”
Section: Discussionmentioning
confidence: 99%
“…P. fumosoroseus is capable of affecting whitefly Aleurodicus cocois at various developmental stages [ 234 ]. Similarly, the physical barriers of Leptinotarsa decemlineata pupae make them more resistant than their larvae to Isaria fumosorosea infection [ 235 ]. In terms of size, Hunter et al [ 236 ] showed a negative correlation between insect mortality and size mainly because larger sizes are associated with thicker cuticles, as in the use of I. fumosorosea on Diaphorina citri (psyllid) and D. citri (curculionidae), in which case the latter is bigger.…”
Section: Biological Control Of Diseases Caused By Arthropodsmentioning
confidence: 99%
“…Numerous orders of arthropods that are vulnerable to the use of Paecilomyces spp. ( Table 3 ), including hemiptera, have been described, such as aleurodids [ 246 ], aphids [ 238 ], thysanoptera [ 242 ], diptera [ 247 ], lepidoptera [ 73 ], hymenoptera [ 248 ] and coleoptera [ 235 ].…”
Section: Biological Control Of Diseases Caused By Arthropodsmentioning
confidence: 99%
“…In an interesting manner, additive or synergistic interactions of the control agent with other species can be exploited for biological control. However, the nature of their interaction (antagonistic or additive/synergistic) depends on, for example, timing (simultaneously or sequential) and rate of application (Hussein, Habustova, Puza, & Zemek, ; Shapiro‐Ilan et al., ).…”
Section: Step 3: Understanding Variation In D Suzukii–parasitoid Intmentioning
confidence: 99%